INVESTIGATING THE OPERATIONAL ISSUE AND POTENTIAL DEMAND OF AIRPORT BUS SERVICE AT MINANGKABAU INTERNATIONAL AIRPORT - Yaldi, Gusri (Jurnal Transportasi, 2014)
Abstract Minangkabau International Airport (BIM) has been operating almost a decade and currently BIM can be visited using the airport bus provided by the City Government of Padang. Although the airport bus service is available, BIM visitors generally tend to choose private vehicles, such as cars or motorcycles. Considering the energy crisis and the negative impact of traffic, visitors are expected to shift to the airport bus, because the bus is more sustainable mode of transportation. However, this policy needs to be supported with sufficient information so that the target to be achieved can be realized. This study aimed to investigate factors that prevent visitors to use the airport bus and try to predict the potential demands. The results obtained from this study show that only 19 % of BIM visitors choose an airport bus as a mode of transportation. Other modes are selected because of some uncertainty on the airport bus service, which involves schedules and bus stop locations. In addition, a number of respondents did not even know of the existence of the airport bus service. If these problems can be solved, the potential airport bus users are predicted to reach 58 % of the total number of BIM visitors. Keywords: airport, airport bus, private vehicles, cars, motorcycles  Abstrak Bandara Internasional Minangkabau (BIM) telah beroperasi hampir satu dekade dan saat ini BIM dapat dikunjungi dengan menggunakan bis bandara yang disediakan oleh Pemerintah Kota Padang. Walaupun tersedia layanan bis bandara, pengunjung BIM umumnya cenderung memilih kendaraan pribadi, seperti mobil atau sepeda motor. Dengan memperhatikan krisis energi dan dampak negatif lalulintas, pengunjung BIM diharapkan dapat berpindah menggunaan bis bandara, karena bis merupakan moda transportasi yang lebih berkelanjutan. Namun kebijakan ini perlu didukung dengan informasi yang cukup sehingga target yang hendak dicapai dapat direalisasikan. Kajian ini bertujuan untuk menginvestigasi faktor-faktor yang menghambat pengunjung BIM untuk menggunakan bis bandara serta mencoba untuk memprediksi potensi kebutuhannya. Hasil yang diperoleh dari kajian ini adalah bahwa hanya 19 % pengunjung BIM memilih bis bandara sebagai moda transportasinya. Moda lain dipilih karena ketidakpastian pada pelayanan bis bandara, yang menyangkut jadwal dan lokasi halte. Selain itu sejumlah responden bahkan tidak mengetahui adanya layanan bis bandara. Jika permasalahan tersebut dapat diatasi, diprediksi potensi pengguna bis bandara dapat mencapai 58 % terhadap jumlah total pengunjung BIM. Kata-kata kunci: bandar udara, bis bandara, kendaraan pribadi, mobil, sepeda motor